ANALISIS IMPLEMENTASI KESIAPAN SEKOLAH DALAM MENGINTEGRASIKAN PRINSIP INKLUSI BAGI ANAK BERKEBUTUHAN KHUSUS - Rama Prasetya; Michelle Diva Shatrani; Muhammad Aji Saputra; Muhammad Rangga Aji Saputra; Nandina Salsabila; Nurul Wildatun Ath Thoyyibah; Swastika Citra Endah Prameswari (STKIP Pesisir Selatan, 2026)
Objective: Equitable access to education for Indonesian society is being realized through inclusive education policy. However, in practice, school readiness to implement this policy remains suboptimal. This study analyzes school readiness in building an inclusive educational environment for children with special needs (CSN). This qualitative study uses a Systematic Literature Review (SLR) approach with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) scheme for article collection and selection. Fifty eligible articles were analyzed using an interactive model comprising data reduction, data display, and conclusion drawing, with validity maintained through source triangulation. Results show that school readiness requires a strong relationship between an adaptive education system, adequate supporting facilities, and active collaboration among school members and external stakeholders to accommodate CSN needs. However, field implementation still faces obstacles, including limited inclusive infrastructure, an insufficient number of special assistant teachers, low teacher competence in inclusive education, and persistent negative stigma in the educational environment. Overcoming these obstacles requires a comprehensive, sustainable strategy focused on improving teacher competency, allocating a specific budget for inclusive facilities, and strengthening internal school policies so that inclusive education can be implemented equitably and sustainably.